Mensuração de desempenho em programas de pós-graduação profissionais: proposição de um framework a partir das novas perspectivas de autoavaliação da CAPES - Silva, Lísias André de Vieira e (2021)
Taking into account the importance of measuring performance in educational activities this research reviews the evolution of graduate studies in Brazil, on performance assessment and strategic planning processes with the intention of proposing a self-assessment framework for the Postgraduate Program in Public Administration (PPGAP) at the Federal University of Lavras, professional modality, based on the use of the Balanced Scorecard tool. To achieve this objective, the management reports of the regulatory body and the research program were reviewed, in addiction an attempt was made to understand the European multidimensional evaluation practice, a Survey was applied to know the local needs, the BSC tool was adapted and elaborated. a brief document suggesting indicatives for self-assessment assembly. As a result of this applied research effort, a framework was created with the potential of coordinating and alignment among objectives and guidelines of CAPES, PPGAP and the local academic community. It is hoped, with the proposition of this framework, to inspire the other PPGs, based on the proposed methodology and making the necessary modifications to assist students, professors, and the community, to create their own self-assessment instruments, thus strengthening the Institution's Graduate Program.